Mid-Trimester Scan is better for Detecting Congenital Anomalies: An Experience from Dhulikhel Hospital - Tamrakar, Suman Raj; Shrestha, Rubina (Journal of Nepalgunj Medical College, 2020)
Introduction: Ultrasound is a valuable diagnostic tool for detecting the congenital anomalies in the fetus. Congenital anomalies are detected in 14% of new born. Major anomalies are detected in 2 to 5% of new born. This accounts for 20 % to 30% of total perinatal deaths. Prenatal diagnosis provides variety of management options for the pregnant women ranging from termination of pregnancy, elective delivery or intrauterine manipulation of the anomalies. Aims: To determine the prevalence of the fetal congenital anomalies at 20- 24 weeks ultrasonography. Methods: This is prospective study conducted at Dhulikhel Hospital. Pregnant ladies with singleton pregnancy at 20 to 24 weeks were enrolled for transabdominal ultrasound for detecting congenital anomalies. Results: Of 1027 pregnant ladies screened, anomalies were detected in 31 ladies during mid trimester ultrasound. The overall prevalence of congenital anomalies detected in our study is 3.02% (31 cases), which has sensitivity of 87.8%, specificity of 99.7% and positive predictive values of 93.5%. In our study, mean gestational age during scan was 21+5 weeks of gestation. And 13 pregnant ladies pregnancies were terminated between 20-24 weeks for having major congenital anomaly in fetus. Conclusion: Mid trimester ultrasonography is a valuable method for pregnant ladies to detect the congenital anomalies in fetus. When major anomalies are detected, timely termination of pregnancy have saved the cost and tragedy of losing viable fetus.